Guimarães Rosa e seus precursores: regionalismo, deslocamentos e ressignificações - André Tessaro Pelinser (2015)
This doctoral thesis can be divided into two main axes. On the one hand, the proposed reflections seek to respond to the need of a 'critique of the criticism' related to the Brazilian literary Regionalism. For such, the study aims at examining in detail some analyses that can be considered representatives of the perspective adopted by Brazilian literary critics regarding the regionalist literary tradition and literary works affiliated to it. It intends to investigate the path taken by Regionalism throughout Brazilian literary history, as well as to review stances conveyed by several specialised studies and, therefore, to reassess some lines of reasoning that guided the constitution of the literary field in Brazil. Thus, this study has the purpose of apprehending part of the aspects that contributed to the hegemony of a set of restrictive perspectives towards regional or regionalist literatures in Brazil. On the other hand, this thesis focuses on the impact represented by the emergence of João Guimarães Rosa's fiction in the Brazilian literary field, emphasising how his literary works resume the regionalist literary tradition and how such a characteristic has been appropriated by art criticism. Bearing this in mind, this study is intended to cast light upon the importance of the imaginary about Regionalism in Brazil when it comes to the production of meanings relating to Guimarães Rosa's literature throughout the development of his critical fortune. It aims at highlighting not only the way Guimarães Rosa internalises and reworks part of the Brazilian literary tradition, but also the effects of the identification of other literary voices in his texts and how literary criticism based on that identification contributed to dislocate the preceding writers. Taking this into account, this study analyses how Guimarães Rosa creates his precursors among the regionalist authors and profits from their vigour in order to create his own poetic strength. At the same time, it examines how Guimarães Rosa's literature redefines the works of his precursors and alters their literary capital, fostering deep rearrangements in Brazilian literary tradition.